2003
DOI: 10.1088/0953-8984/15/36/311
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and electronic properties of strontium hexaferrite SrFe12O19from first-principles calculations

Abstract: The magnetic and electronic structure of strontium hexaferrite SrFe 12 O 19 has been investigated using density functional theory within the local spin density approximation. The calculations show that in this ferrite all the Fe 3+ ions are fully spin polarized with S = 5/2. The electronic structure of this ferrite is strongly influenced by the exchange interactions between the iron ions. The most stable form of the ferrite is a ferrimagnet with the Fe 3+ ions at the 4f sites having their spin polarization ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 26 publications
2
49
0
1
Order By: Relevance
“…Many scientists preceded their research work on investigation of crystal structure of SrFe 12 O 19 and reported their detailed results. For instance, Fang et al [10] determined the crystal structure of SrFe 12 O 19 using density functional theory. The crystallographers have determined that the crystal structure of SrFe 12 O 19 is hexagonal.…”
Section: Introductionmentioning
confidence: 99%
“…Many scientists preceded their research work on investigation of crystal structure of SrFe 12 O 19 and reported their detailed results. For instance, Fang et al [10] determined the crystal structure of SrFe 12 O 19 using density functional theory. The crystallographers have determined that the crystal structure of SrFe 12 O 19 is hexagonal.…”
Section: Introductionmentioning
confidence: 99%
“…38 In ferrites, the conduction is because of electron hopping from Fe 2+ and Fe 3+ ions present at octahedral (B) sites. [39][40][41] The presence of Fe 2+ also contributes a lot to the dielectric properties of ferrites. So, the presence of Fe 2+ ions in hexaferrites is the source of charge carriers and is responsible for the conduction mechanism in ferrites.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…The hexagonal ferrite type-M is denoted by the formula MFe 12 O 19 , where M is a divalent metal ion, typically Sr 2+ , Ba 2+ , or Pb 2+ [2]. Since its discovery in 1950 [3], the hexagonal ferrite type-M SrFe 12 O 19 has played an important role in hard magnetic materials and has been studied for decades due to its good chemical stability, ferrimagnetic behavior, high Curie temperature, high saturation magnetization, high coercivity, high magneto-crystalline anisotropy (MCA), and it is inexpensive compared to similar compounds [4][5][6]. As it has magnetization values of about 60 Am 2 /kg and coercivity of 4.37 × 10 5 A/m, it is widely used in magnetic recording material, data storage devices [7], magneto-optical recordings, microwave devices [8], permanent magnets, and electromagnetic devices [9].…”
Section: Introductionmentioning
confidence: 99%